1982
DOI: 10.1007/bf00378160
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of urinary 2-thio-thiazolidine-4-carboxylic-acid (TTCA) levels as a test for exposure to carbon disulfide

Abstract: The exposure to carbon disulfide of workers in charge of different jobs in a Belgian viscose plant was measured by means of personal monitoring of the inhaled air and by quantitative assay of 2-thio-thiazolidine-4-carboxylic acid (TTCA) in urine. It was found that the atmospheric carbon disulfide concentration varied considerably among different jobs, among different individuals doing the same jobs and for the same individuals in the course of the working period. The 2-thio-thiazolidine-4-carboxylic-acid level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…These job duties and process are described elsewhere [Hampel and Hawley, 1973;Boillat, 1979;Rosier et al, 1982;Vanhoorne et al, 1991]. The NIOSH industrial hygienist classified all workload levels as near at-rest to moderate (100W).…”
Section: Exposed Workers and Unit Processesmentioning
confidence: 99%
“…These job duties and process are described elsewhere [Hampel and Hawley, 1973;Boillat, 1979;Rosier et al, 1982;Vanhoorne et al, 1991]. The NIOSH industrial hygienist classified all workload levels as near at-rest to moderate (100W).…”
Section: Exposed Workers and Unit Processesmentioning
confidence: 99%
“…Rosier et al reported a half-life of two hours for six human volunteers exposed to CS 2 at concentrations of 10 or 20 ppm (Rosier et al, 1987). In other reports regarding the workers occupationally exposed to CS 2 at 33 ppm, Rosier found traces of urinary TTCA up to 64 hours and concluded that the excretion is at least biphasic (Rosier et al, 1982;1984). Previous reports, however, were simply based on one-hit study design, i.e., the environmental exposure and urine levels were monitored simultaneously and only once or at most twice.…”
Section: Introductionmentioning
confidence: 90%
“…The current BEI is based on limited information obtained from the field studies of Campbell et al (1985) and van D oorn et al (1981b). H owever, Rosier and colleagues have demonstrated a markedly projected U -TTCA BEI value at the CS 2 exposed level of 10 ppm (Rosier et al, 1982;1984).…”
Section: Introductionmentioning
confidence: 96%
“…Most existing TTCA assays are based on high performance liquid chromatography (HPLC) with ultraviolet detection [3, 6,11,141 or capillary gas chromatography with thermionic detection [GI. A serious inconvenience of the HPLC methods is the need for time-consuming extraction steps and complicating gradient elution programs needed to reduce interferences from common urine constituents.…”
Section: Iatroducy7oivmentioning
confidence: 99%